Differential Suppression of Spontaneous and Noxious-evoked Somatosensory Cortical Activity by Isoflurane in the Neonatal Rat. (April 2016) - Chang, Pi-shan; Walker, Suellen M.; Fitzgerald, Maria
Abstract : Background: The effect of neonatal anesthesia and pain on the developing brain is of considerable clinical importance, but few studies have evaluated noxious surgical input to the infant brain under anesthesia. Herein, the authors tested the effect of increasing isoflurane concentration on spontaneous and evoked nociceptive activity in the somatosensory cortex of rats at different postnatal ages. Methods: Intracortical extracellular field potentials evoked by hind paw C-fiber electrical stimulation were recorded in the rat somatosensory cortex at postnatal day (P) 7, P14, P21, and P30 during isoflurane anesthesia (n = 7 per group). The amplitudes of evoked potentials and the energies of evoked oscillations (1 to 100 Hz over 3 s) were measured after equilibration at 1.5% isoflurane and during step increases in inspired isoflurane. Responses during and after plantar hind paw incision were compared at P7 and P30 (n = 6 per group). Results: At P7, cortical activity was silent at 1.5% isoflurane but noxious-evoked potentials decreased only gradually in amplitude and energy with step increases in isoflurane. The resistance of noxious-evoked potentials to isoflurane at P7 was significantly enhanced after surgical hind paw incision (69 ± 16% vs . 6 ± 1% in nonincised animals at maximum inspired isoflurane). This resistance was age dependent; at P14 to P30, noxious-evoked responses decreased sharply with increasing isoflurane (step 3 [4%] P7: 50 ± 9%, P30: 4 ± 1% of baseline). Hind paw incision at P30 sensitized noxious-evoked potentials, but this was suppressed by higher isoflurane concentrations. Conclusions: Despite suppression of spontaneous activity, cortical-evoked potentials are more resistant to isoflurane in young rats and are further sensitized by surgical injury. Abstract : Extracellular somatosensory cortex field potentials evoked by hind paw C-fiber electrical stimulation were resistant to isoflurane compared with spontaneous activity in neonatal rat. Surgical hind paw incision enhanced the resistance of noxious-evoked responses to isoflurane, an effect that declined with age, indicating critical age-dependent differences in anesthetic suppression of cortical nociceptive activity.